Imagery rescripting in individuals with binge‐eating behavior: An experimental proof‐of‐concept study. Issue 2 (31st December 2018) - Dugué, Rebecca; Renner, Fritz; Austermann, Marit; Tuschen‐Caffier, Brunna; Jacob, Gitta A.
Abstract: Objective: Mental imagery is more strongly related to emotions than verbal cognitions. Binge eating is associated with dysfunctional emotional regulation. However, cognitive therapy techniques have focused on verbal cognitions. This proof‐of‐concept study compares a traditional cognitive therapy technique, cognitive restructuring (CR), with imagery rescripting (IR) in individuals with binge‐eating disorder or bulimia nervosa. Method: Thirty‐six participants were asked to recall an idiosyncratic mental image of social rejection. They were then randomly assigned to a single session of CR or IR. Ratings of positive and negative emotions, and impact on rational and emotional core beliefs were administered prior to and after imagery recall, after the experimental intervention, and 1 week later. Eating disorder psychopathology was measured before and 1 week after the experimental intervention. Results: Repeated measures ANOVAs revealed that after the experimental intervention, negative emotions and core beliefs had significantly decreased in CR and IR. Both groups also showed an increase in positive emotions that lasted until 1‐week follow‐up. Discussion: This study suggests that CR and IR as an experimental intervention have comparable impact on distress and rational and emotional core beliefs. The feasibility of IR has been demonstrated. The effect of imagery recall on CR needs further investigation.